Dialect Words Regarding Chukurak Village, Varganza City, Book District. - Saidova Mahzuna Farhod's Qizi (Euro Asian Journal Publishing, 2024)
This article contains words related to the dialect that serve as a basis for the enrichment of our mother tongue. These words are dialects of Chukurak village, Kitob district, Kashkadarya region, Varganza town
Keywords: dialect; Kitab; Varganza